Interaction of the smooth endoplasmic reticulum and mitochondria. (22nd May 2006) - Goetz, J.G.; Nabi, I.R.
Abstract : The ER (endoplasmic reticulum) is composed of multiple domains including the nuclear envelope, ribosome-studded rough ER and the SER (smooth ER). The SER can also be functionally segregated into domains that regulate ER–Golgi traffic (transitional ER), ERAD (ER-associated degradation), sterol and lipid biosynthesis and calcium sequestration. The last two, as well as apoptosis, are critically regulated by the close association of the SER with mitochondria. Studies with AMFR (autocrine motility factor receptor) have defined an SER domain whose integrity and mitochondrial association can be modulated by ilimaquinone as well as by free cytosolic calcium levels in the normal physiological range. AMFR is an E3 ubiquitin ligase that targets its ligand directly to the SER via a caveolae/raft-dependent pathway. In the present review, we will address the relationship between the calcium-dependent morphology and mitochondrial association of the SER and its various functional roles in the cell.